Overlap between birth trauma and mistreatment: a qualitative analysis exploring American clinician perspectives on patient birth experiences - Cynthia Salter; Kristina Wint; Jessica Burke; Judy C. Chang; Patricia Documet; Elizabeth Kaselitz; Dara Mendez (BMC, 2023)
Abstract Introduction Research exploring the mistreatment of birthing people in the United States is emerging rapidly within the context of increasingly poor maternal health outcomes that include unacceptable racial disparities. Previous research has explored overlap between psychological birth trauma and mistreatment using patient descriptions of birth experiences, but no previous studies have explored these issues from the perspectives of clinicians. The aim of this study was to explore whether maternity care providers' descriptions of patient birth trauma overlap with categories of mistreatment from a globally accepted typology. Methods Content analysis was performed on a qualitative data set of 28 semi-structured interviews about patient birth trauma, completed in 2018-2019 with U.S. maternity care clinicians, including obstetricians, family physicians, midwives and labor/delivery nurses. The interviews were part of a larger study exploring maternity clinician perspectives and experiences of patient birth trauma. For this analysis Krippendorff's method of categoric distinction was used, with categories from a globally recognized typology of maternity patient mistreatment. Results Clinicians' descriptions of their experiences with patient birth trauma mapped onto all seven mistreatment categories, although no interview questions specifically asked about mistreatment. In more than 30 hours of interviews, transcribed to more than 800 pages, the word mistreatment appears only once, suggesting that some healthcare providers may use the phrase "birth trauma" as a euphemism to describe mistreatment. Eighteen of 28 interviews included at least one description that fit into a mistreatment category. "Failure to meet professional standards of care" was the category with the most mapped clinician statements, followed by "Stigma and discrimination" and "Poor rapport between women and providers." Conclusions This study contributes new insight into maternity clinicians' conceptualization of patient trauma and how their descriptions of birth trauma overlap with mistreatment. Clinicians implicitly connected mistreatment with some patient experiences of birth trauma, even when they were not specifically asked about mistreatment. Findings point to a need for further research into mistreatment, including routinized "everyday care" that may include mistreatment, particularly for marginalized and historically excluded birthing people. Future research also must explore the potential role of mistreatment in poor and inequitable U.S. birth outcomes.